Most Favoured Nation Clause: Unleashing its Legal Potential in Favour of Foreign Investors in Renewable Energy Sector - Ghaziani, Mohammad Akefi; Ghaziani, Vahid Akefi; Ghaziani, Moosa Akefi, Dr. (UI Scholars Hub, 2022)
International Investment Law and other international legal systems, such as trade law and environmental law have interactions and dynamic interrelationships in meeting global challenges including energy security, climate change, and the need for the renewable energy transition. They help in delivering the principles of justice in the context of changing global values and legal practices. Accordingly, they have a potential share in the global climate change mitigation agenda through innovative policies and regulations, inter alia, to facilitate and promote foreign investment and trade in the renewable energy sector. Similarly, these systems have common principles in their respective agreements. The Most-Favoured Nation Treatment (MFN) is among these. Hence to analyse the potential role of MFN in the context of the renewable energy transition is significant. This article sheds light on this dilemma by expounding on the concept of MFN, analysing the MFN clauses under IIAs, and its relevance in terms of renewable energy investment protection. It concludes that the application of MFN has been especially problematic since it is incorporated somewhat differently in the international investment and trade regimes. While it is one of the basic principles of WTO, it remains among the least successful provisions in investor-State arbitration. Despite its nearly ubiquitous usage, the interpretation of the MFN clause and its scope of application has been disputable so far. IIAs contain different MFN clauses with various exemptions, and the arbitral practice has demonstrated several divergent decisions that other tribunals and legal scholars feel should be subject to a more focused review.